The protective effect of hydroalcoholic extract of Ginger (Zingiber officinale Rosc.) against iron-induced functional and histological damages in rat liver and kidney - Firouzeh Gholampour; Fatemeh Behzadi Ghiasabadi; Seyed Mohammad Owji; Jaafar Vatanparast (Mashhad University of Medical Sciences, 2017)
Objective: Iron overload in the body is related with toxic effects and threatens the health. The aim of this study was to evaluate the protective role of hydroalcoholic extract of ginger (Zingiber officinale) against ferrous sulfate-induced hepatic and renal functional disorders and histological damages in rats. Materials and Methods: The rats were divided into four groups (n=7): Sham, Sham + G.E (ginger extract, 400 mg/kg/day for 14 days), FS (ferrous sulfate, 30 mg/kg/day for 14 days), FS+G.E (ferrous sulfate, 30 mg/kg/day for 14 days; ginger extract, 400 mg/kg/day for 11 days from the fourth day of ferrous sulfate injection). After 24 hr, blood, urine and tissue samples were collected. Results: Compared with Sham and Sham + G.E groups, administration of ferrous sulfate resulted in liver and kidney dysfunction as evidenced by significantly higher levels of serum hepatic markers and bilirubin, and lower levels of serum albumin, total protein, triglyceride, cholesterol and glucose, as well as lower creatinine clearance and higher fractional excretion of sodium (p